Impact of the modality of mechanical ventilation on bleeding during pituitary surgery: A single blinded randomized trial. Issue 38 (September 2019) - Le Guen, Morgan; Paternot, Alexis; Declerck, Agnes; Feliot, Elodie; Gayat, Etienne; Gaillard, Stephan; Fischler, Marc
Abstract: Background: Bleeding modifies the surgeon's view of the field during transsphenoidal endoscopic pituitary surgery. Since ventilation can alter venous return, we compared the effect of volume-controlled ventilation (VCV) and pressure-controlled ventilation (PCV) on intraoperative bleeding. Methods: Eighty-six patients were randomized to VCV or PCV in this single blinded study; comparisons concerned 42 in the PCV group and 43 in the VCV group. Results: Intraoperative bleeding, the primary endpoint, did not differ between groups whether analysis focused on 7 levels of the score, from minimal bleeding to bleeding with significant change in the conduct of surgical procedure ( P = .89) or on a stratification into 3 categories, mild, moderate, and major ( P = .47). Median [interquartile range] peak airway pressure was lower in the PCV group (13.5 [12.5–15] vs 16.3 [14.4–19.1] cm H2 O, P < .001) while mean airway pressures were similar ( P = .08). Means ± SD of tidal volumes were lower in the VCV group when expressed as absolute values (470.6 ± 84 vs 434.7 ± 71.7 ml, P = .05) or as tidal volume/theoretical ideal weight ratio (6.7 [6.5–7] vs 7.2 [6.9–7.9], P < .001). The 2 groups were similar for postoperative complications and number of patients cured. Conclusion: In conclusion, ventilation mode does not influence intraoperative bleeding during transsphenoidal pituitary surgery. Trial registration: Clinicaltrials.gov identifier: NCT01891838; July 3, 2013